Increased calcium-independent phospholipase A2 activity in first but not in multiepisode chronic schizophrenia - Smesny, Stefan; Kinder, Daniel; Willhardt, Ingo; Rosburg, Timm; Lasch, Jürgen; Berger, Gregor; Sauer, Heinrich (Biological psychiatry (1969), 2005)
Increased activity of calcium independent phospholipase A2 (iPLA2) has repeatedly been found in the serum of unmedicated first-episode schizophrenia patients and assumed to reflect a pertubation of phospholipid metabolism. Previous studies in chronic schizophrenia were less conclusive. To explore whether iPLA2 changes are stage dependent, we investigated serum iPLA2 activity in various stages of schizophrenia. iPLA2 activity was assessed in the serum of 30 first-episode and 23 multiepisode schizophrenia patients and 53 healthy control subjects matched for age and gender. A fluorimetric assay was applied using the PLA2 specific substrate NBDC6-HPC, thin-layer chromatography of reaction products, and digital image scanning for signal detection. Group comparison between first-episode and multiepisode patients and corresponding control groups revealed significantly increased iPLA2 activity only in first-episode patients. Enzyme activity in first-episode patients was also markedly increased, compared with chronic patients. iPLA2 changes observed were irrespective of neuroleptic medication, age, or gender. Our results suggest increased lipid turnover in the acute early phase of schizophrenia that is less obvious in chronic stages. Future longitudinal studies involving iPLA2 activity and phosphorous magnetic resonance spectroscopy need to address the relation between perturbed brain lipid metabolism and iPLA2 increment in the course of schizophrenia.